До питання про якість законів у контексті відповідальності парламенту - Бакумов, О. С.; Bakumov, O. S. (Jurnalul juridic national: teorie şi practică = Национальный юридический журнал: теория и практика. - 2019. - № 4, ч. 1 (August ). - С. 25-31, 2019)
У статті розглянуто актуальні питання посилення відповідальності Верховної Ради України у сфері законотворення. Доведено, що це питання є одним з ключових питань парламентської реформи. Проаналізовано основні недоліки у законодавчій діяльності парламенту України: надмірний законодавчий активізм; відсутність планування, передбачуваності та правового моніторингу законодавства; не досить послідовна координація законодавчих зусиль між парламентом і Урядом, відсутність фінансового обґрунтування законів. Запропоновано напрями зміцнення позитивної відповідальності парламенту у законодавчій сфері: розгляд законопроєктів парламентом лише за умови обов’язкового, а не факультативного проведення їх попередньої експертизи Кабінетом Міністрів України; підвищення статусу експертних висновків науково-експертного та юридичного підрозділів апарату Верховної Ради України; надання комітетам Верховної Ради України права самостійно об’єднувати близькі за предметом регулювання законопроєкти перед другим читанням; визначення вичерпного переліку випадків, за яких обговорення законопроєктів може здійснюватися за скороченою процедурою.

In the article the pressing questions of strengthening of responsibility of Verkhovna Rada of Ukraine are considered in the field of law-making. It is well-proven that this question is one of key questions of parliamentary reform. The key failings are analyzed in legislative activity of parliament of Ukraine: excessive legislative activity; absence of planning, predictableness and legal monitoring of legislation; not enough successive co-ordination of legislative efforts between legislators and Government, absence of financial validity of laws. The followings directions of strengthening positive responsibility of parliament are offered in a legislative sphere: consideration of bills parliament only on condition of obligatory, but not optional leadthrough of their preliminary examination by Cabinet of Ministers of Ukraine; increase of status of expert conclusions of scientific-expert and legal subdivisions of vehicle of Verkhovna Rada of Ukraine; grant the committees of Verkhovna Rada of Ukraine of right independently to unite near on the article of adjusting bills before the second reading; determination of exhaustive list of cases at which the discussion of bills can be carried out on brief procedure.

В статье рассмотрены актуальные вопросы усиления ответственности Верховной Рады Украины в сфере законообразования. Доказано, что этот вопрос является одним из ключевых вопросов парламентской реформы. Проанализированы основные недостатки в законодательной деятельности парламента Украины: чрезмерный законодательный активизм; отсутствие планирования, предсказуемости и правового мониторинга законодательства; недостаточно последовательная координация законодательных усилий между парламентом и правительством, отсутствие финансового обоснования законов.
Responsibility of parliament of Ukraine for passing high-quality acts: constitutional-legal analysis
Keywords: парламент; юридична відповідальність; народний депутат; Верховна Рада України; Уряд; parliament; legal responsibility; people’s deputy; Verkhovna Rada of Ukraine; Government; юридическая ответственность; народный депутат; Верховная Рада Украины; правительство